PEMAHAMAN MAHASISWA CALON GURU FISIKA DALAM MENGINTERPRETASIKAN GRAFIK PADA KONSEP TERMODINAMIKA - Farhana, Widad; Pasaribu, Marungkil; Syamsu (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2021)
This study aims to determine the understanding of prospective physics teacher students in interpreting graphs on the concept of thermodynamics. Respondents in this study consisted of 18 students of third-semester physics teacher candidates, Physics Education Study Program, Department of Mathematics and Natural Sciences, Faculty of Teacher Training and Education, Tadulako University. The instrument used is an essay test that consists of 6 questions. The data obtained were analyzed through a descriptive-qualitative approach by referring to the results of the answers using the Thinking-aloud method and student interviews with questions in interpreting graphs on the concept of thermodynamics. The results showed that the understanding of prospective physics teacher students was still relatively low with an average percentage of 24.53%. Student understanding is measured by 3 descriptors, the ability to translate descriptors is in a low category, namely 42.36%, the ability to interpret descriptors is in the very low category of 27.77% while the predictor ability descriptors are also very low at 3.47%. In general, prospective physics teacher students are still lacking in understanding graphs on thermodynamic concepts.